Phytopharmacological Insights into Ricinus communis: A Comprehensive Overview - Surya Nath Pandey; Prashant Kumar; Harishchandra Verma; Sumit Durgapal; Balwan Singh (Pharmacognosy Research, 2025)
Medicinal plants are used in the traditional medicinal system and in Ayurveda globally. Euphorbiaceae is a large family which contains more than 3000 species. Ricinus communis or castor bean plant is well-known plant of Ayurveda. The herbal and natural medicines are the cost-effective and they have lesser side effects than currently available medicines in the market. Ricinus communis has many phytoconstituents such as ricinine, ricin A, ricin B, ricin C, ricinoleic acid, Y-sitosterol, fucosterol, stigmasterol, ricinus agglutin etc. which are responsible for various pharmacological activities. Traditionally, it has various pharmacological properties such as antioxidant activity, antifertility activity, antiulcer activity, antidiabetic activity, antimicrobial activity, hepatoprotective activity, immunomodulatory activity, bone regeneration activity, cytotoxic activity, anti-inflammatory activity etc. They also exhibited free radical scavenging potential along with repellent properties. The main objective of this review is to reveal all updated information’s like phytochemicals, pharmacological activities of Ricinus communis by scientific evidences.
Keywords: Herbal Medicines; Medicinal plants; Pharmacological activities; Phytochemicals; Ricinus communis